2017
DOI: 10.1021/acs.jproteome.7b00279
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Acylcarnitines in First Episode Psychosis before and after Antipsychotic Treatment

Abstract: Acylcarnitines (ACs) have been shown to have a potential to activate pro-inflammatory signaling pathways and to foster the development of insulin resistance. The first task of the current study was to study the full list of ACs (from C2 to C18) in first episode psychosis (FEP) patients before and after antipsychotic treatment. The second task was to relate ACs to inflammatory and metabolic biomarkers established in the same patient cohort as in our previous studies. Serum levels of ACs were determined with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 49 publications
7
46
0
Order By: Relevance
“…Therefore, changes in lipids have been associated with the pathophysiology of schizophrenia. Specifically, alterations related to fatty acids and ketone bodies 55 , 56 , phospholipids 57 , 58 sphingolipids 59 , total lipids, triglycerides and cholesterol esters were observed in schizophrenia patients 60 62 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, changes in lipids have been associated with the pathophysiology of schizophrenia. Specifically, alterations related to fatty acids and ketone bodies 55 , 56 , phospholipids 57 , 58 sphingolipids 59 , total lipids, triglycerides and cholesterol esters were observed in schizophrenia patients 60 62 .…”
Section: Resultsmentioning
confidence: 98%
“…Regarding antipsychotics, studies have suggested that these drugs may compensate for or reverse lipid pathway dysregulation related to the early stage of the disorder 55,59,63 . Furthermore, fatty acid metabolism and cholesterol biosynthesis have been identified by gene expression studies as key elements in antipsychotic treatment response 64,65 .…”
Section: Resultsmentioning
confidence: 99%
“…There are also a small number of studies used GC-MS [88]. In recent years, LC-MS has become the most popular techniques for acylcarnitine detection [89,90,91,92,93]. Reversed-phase liquid chromatography (RPLC), hydrophilic interaction liquid chromatography (HILIC), ion chromatography, and capillary electrophoresis are different options for acylcarnitine separation.…”
Section: Detection Of Acylcarnitines In Biological Samplesmentioning
confidence: 99%
“…Carnitine and acyl-carnitine supplementation have also been used in the treatment of various illnesses (e.g., Alzheimer’s disease, peripheral arterial disease, and celiac disease) for decades with the primary function of regulating cellular bioenergetics 19,20 . Furthermore, accumulated evidence indicates that alterations of carnitines may contribute to certain mental illnesses, including depression 21 , autism spectrum disorder 22 , and schizophrenia 23 . In particular, several recent studies have reported that schizophrenia is associated with an imbalance in redox or oxidative stress status.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acetyl-carnitine and levocarnitine 26,27 supplementation therapies have been used to target carnitine deficiency observed in individuals with schizophrenia. Available evidence suggest that acyl-carnitines impact insulin sensitivity, lipid metabolism, inflammatory response, as well as bioenergetic functions 23,28 . Based on these foregoing evidence, we believe acyl-carnitines play an essential role in the pathoetiology of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%